Insight into the Anchoring Effect of Two‐Dimensional TiX2 (X = S, Se) Materials for Sodium–Sulfur Batteries: A First‐Principles Study. Issue 3 (31st January 2023) - Zheng, Yunxin; Wang, Yanwen; Xiao, Jianrong; Xu, Liang; Dai, Xueqiong; Wang, Zhiyong
Abstract: In this paper, a monolayer of TiX2 (X = S, Se) is used to suppress the shuttle effect of polysulfides, thereby accelerating the kinetic process of lower‐order polysulfides. The results show that the adsorption energies of the studied TiX2 for Na2 Sn are all better than those of common electrolytes, and the effect of adsorption on the structure of Na2 Sn is negligible. The calculated results show that the anchoring behavior of TiX2 to Na2 Sn has no effect on the metallic properties of pristine TiX2 . On the other hand, the introduction of this material can reduce the diffusion barrier energy of Na2 S and improve the utilization rate of sulfur more effectively. In conclusion, TiX2 has suitable adsorption strength, enhances electrical conductivity, and promotes the oxidative decomposition process of polysulfides. It can be theoretically demonstrated that TiS2 is better than TiSe2 in improving the performance of sodium–sulfur batteries and is more suitable as an anchoring material (AM) for sodium–sulfur batteries. Abstract : In order to overcome the challenges of "shuttle effect" faced by sodium–sulfur batteries, such as slow decomposition of solid Na2 S, this work introduces single‐layer TiX2 (X = S, Se) as the anchoring material (AM). Studies have shown that TiX2 (X = S, Se) has strong adsorption behavior, enhance the electronic conductivity, can be considered as an effective AM, improve the performance of Na–S batteries.